The WASA core catalogue of Late Quaternary depositional sequences in the central Wadden Sea – A manual for the core repository. (28th February 2022) - Capperucci, Ruggero M.; Bartholomä, Alexander; Bungenstock, Friederike; Enters, Dirk; Karle, Martina; Wehrmann, Achim
Abstract: The reconstruction of submerged palaeolandscapes and detection of settling surfaces along coastal zones became a major research topic within the last two decades. In this context, the WASA project made use of a multidisciplinary approach for defining the extension and describing the characteristics of the Late Pleistocene to Holocene deposits in the central Wadden Sea region. In addition to sub-bottom transects, more than 140 sediment cores were taken in such an area for stratigraphic reconstruction, making use of multi-proxy analysis. To harmonize these data with the existing regional core database (LBEG archive) a new core catalogue was developed, that allows the identification of the local Late Quaternary sedimentary sequences and their characteristic facies. The WASA core catalogue has been successfully applied for reviewing the published data about the stratigraphic sequence of the Wadden Sea, for a better definition in terms of stratigraphic sequences and spatial extent of the Quaternary geological evolution of the region, and for a detailed reconstruction of the coastal palaeoenvironments.